Upaya Penanggulangan Tindak Pidana Korupsi di Indonesia - Fathur Rachman (Universitas Bandar Lampung (UBL), 2018)
Corruption cannot be formulated in just one sentence which might be to make a reasonable picture of these symptoms so that we can separate them from other symptoms that are not corruption. The essence of corruption is the misuse of trust for personal interests. Brooks's formulation of corruption is